Introduction to engineering thermodynamics / Richard E. Sonntag, Claus Borgnakke. - Sonntag, Richard E. (Richard Edwin) (Wiley, 2001)
This volume guides readers step-by-step, from readily measured thermodynamic properties to more complex topics, such as internal energy, entropy, and the first and second laws. It includes examples and real-world problems throughout